2022
DOI: 10.3390/ijms23042132
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation on the ESIPT Process and Detection Mechanism for Dual-Proton Type Fluorescent Probe

Abstract: Recently, a new fluorescent probeAE-Phoswas reported to detect the activity of alkaline phosphatases (ALP) in different living cell lines. Here, we present an in-depth computational analysis of the mechanism and source of the fluorescence of the AE-Phos probe. There is an intermediate product (AE-OH-Phos) in the experiment as well as a different configuration of products that may emit fluorescence. It is essential to investigate the origin of fluorescence and the detection mechanism of the probe, which could h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…In the S 1 state, the di-keto isomer is higher by 4690 cm –1 than the enol isomer and 5490 cm –1 than the keto isomer (we call the mono-keto isomer simply the keto isomer). Therefore, the keto isomer should be the dominant product as reported previously, , while keto and di-keto isomers are supposed to emit at similar wavelengths. The enol isomer in the ground state may have trans or gauche conformations concerning the central N–N bond.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In the S 1 state, the di-keto isomer is higher by 4690 cm –1 than the enol isomer and 5490 cm –1 than the keto isomer (we call the mono-keto isomer simply the keto isomer). Therefore, the keto isomer should be the dominant product as reported previously, , while keto and di-keto isomers are supposed to emit at similar wavelengths. The enol isomer in the ground state may have trans or gauche conformations concerning the central N–N bond.…”
Section: Resultssupporting
confidence: 58%
“…SAA also shows aggregation-induced emission, which, in conjunction with the ESIPT, has been exploited for fluorescence turn-on probe and cellular imaging. , It was reported that photoexcitation produces an excited cis-keto isomer, which returns to the ground state or undergoes twisting motion to form a trans-keto isomer. ,, The ESIPT time constants of salicylaldehyde (SA) and SAA were estimated to be faster than 50 fs (80 fs in ref ) by Ziolek et al, , whereas it was estimated to be 200–300 fs by Mitra and Tamai . SAA was suggested to undergo single proton transfer, although it has two equivalent channels of ESIPT, as shown in Scheme . , Molecules with two possible ESIPT sites that may allow excited-state intramolecular double proton transfer (ESIDPT) are interesting, but the mechanism of the double proton transfer, which can be concerted or stepwise, has been poorly investigated. Determination of accurate reaction rate and recording of the NWPs of the product state(s), which could be the enol, mono-keto, and di-keto isomers, are essential to investigate the molecular dynamics of the ESIPT and ESIDPT. In particular, identification of the product state is critical, and CVSF should be a unique tool because a vibrational spectrum descended from the emission spectrum can be recorded exclusively.…”
Section: Introductionmentioning
confidence: 99%
“…It was well-known that the charge redistribution phenomenon after molecular excitation could directly reflect the excited-state behavior of molecules. 50 Therefore, the transition properties are displayed in Table 5.…”
Section: Charge Reorganizationmentioning
confidence: 99%
“…[58] The analysis of Non-Covalent Interactions (NCI) allows a further refinement of the description. [59] For this, the Reduced Density Gradient (RDG) methodology is popular, [60] as the visual inspection of the scatter plots directly gives an indication of the interactions strength. [61] Additionally, the tautomerization energy gap in the ground and excited states is a useful information for distinguishing ground-state (intramolecular) proton transfer (GSIPT) from ESIPT, and to explain differences in the photophysical properties of closely related dyes.…”
Section: Computer-assisted Decoding Esptmentioning
confidence: 99%
“…The analysis of Non‐Covalent Interactions (NCI) allows a further refinement of the description [59] . For this, the Reduced Density Gradient (RDG) methodology is popular, [60] as the visual inspection of the scatter plots directly gives an indication of the interactions strength [61] …”
Section: Pattern Recognitionmentioning
confidence: 99%